Implementation of innovations in the public administration system for the social sphere: reform of the deinstitutionalization process in Ukraine - Melnychuk, L.; Hohol, T.; Gorinov, P. (Public Policy and Accounting, 2021)
The main purpose of the research is to identify problems of public administration in the context of achieving strategic goals of the deinstitutionalization process for children’s social care in Ukraine to ultimately implement innovative changes in the children’s social care. In terms of the theory and practice of public administration in Ukraine these issues remain unresolved and require further development and research. The article examines the reform of the national system of institutional child care in the following logical sequence: analysis of the main stages of the reform of the deinstitutionalization process for the children’s social care starting from the Ukraine’s independence; assessment of the results of the reform and the level of its efficiency; identification of problems of public administration in the context of achieving the strategic goals of the reform of the deinstitutionalization process for children’s social care in Ukraine; development of proposals for the adaptation of public administration system for the children’s social protection to comply with the European standards. The article provides an analytical review of the implementation of the reform of deinstitutionalization process of child care and showed the gap between the current model of child care deinstitutionalization in Ukraine with today’s needs that requires a radical change in the priorities of public policy for the social care sphere. As the results of the research process the authors have proposed the main directions for the implementation of innovations in the public administration system for the children’s social care, namely: introduction of multilevel governance; creation of a new network of social care institutions both in the territorial dimension and in the functional direction; introduction of new tools for social investment. The achieved results may serve as a basis for further research on modernization of public administration for the children’s social care.